Nonlinear and spatially heterogeneous carbon effects of three-dimensional urban expansion in China - Zilin Deng; Ziyan Luo; Linna Li; Yueting Ma; Yaqun Liu (Environmental Impact Assessment Review, 2026)

Synergistic application of biochar and compound microbial inoculant improves the performance of green waste composting - Cong Luo; Lu Zhang; Linna Suo; Lina Liang (Journal of Environmental Management, 2026)

Structural and functional alterations of human serum albumin (HSA) induced by TBBPS-BME: A spectroscopic, computational, and molecular dynamics study - Wei Zhang; Linna Gao; Shuyuan Zhang; Jiaqing Luo; Ruoxuan Yu; Xiting Li; Zhili Lu; Baozhu Chi; Ying Guo; Xun Tuo (Chemico-Biological Interactions, 2025)

Associations of ambient air pollution with incidence and dynamic progression of atrial fibrillation - Junguo Zhang; Linna Luo; Ge Chen; Baozhuo Ai; Gan Wu; Yanhui Gao; Gregory Y.H. Lip; Hualiang Lin; Yangxin Chen (Science of The Total Environment, 2024)

The benzothiadiazole-based COF/CNT composite as host for efficient Li-S batteries with excellent cycling stability - Guimei Huang; Haoyu Yin; Kangkang Jia; Yuansheng Luo; Jingfu Chen; Cheng Zhong; Linna Zhu; Fei Wu (Chemical Engineering Journal, 2024)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Recognition of Mycobacterium tuberculosis by macrophage Toll-like receptor and its role in autophagy - Linna Wei; Liping Liu; Zudi Meng; Kai Qi; Xuehan Gao; Jihong Feng; Junmin Luo (Inflammation Research, 2024)

Mutant p53R211* ameliorates inflammatory arthritis in AIA rats via inhibition of TBK1-IRF3 innate immune response - Yaling Zeng; Jerome P. L. Ng; Linna Wang; Xiongfei Xu; Betty Yuen Kwan Law; Guobing Chen; Hang Hong Lo; Lijun Yang; Jiujie Yang; Lei Zhang; Liqun Qu; Xiaoyun Yun; et al. (Inflammation Research, 2023)
Background Rheumatoid arthritis (RA) is an autoimmune inflammation disease characterized by imbalance of immune homeostasis. p53 mutants are commonly described as the guardian of cancer cells by conferring them drug-resistance and immune evasion. Importantly, p53 mutations have also been identified in RA patients, and this prompts the investigation of its role in RA pathogenesis. Methods The cytotoxicity of disease-modifying anti-rheumatic drugs (DMARDs) against p53 wild-type (WT)/mutant -transfected RA fibroblast-like synoviocytes (RAFLSs) was evaluated by MTT assay. Adeno-associated virus (AAV) was employed to establish p53 WT/R211* adjuvant-induced arthritis (AIA) rat model. The arthritic condition of rats was assessed by various parameters such as micro-CT analysis. Knee joint samples were isolated for total RNA sequencing analysis. The expressions of cytokines and immune-related genes were examined by qPCR, ELISA assay and immunofluorescence. The mechanistic pathway was determined by immunoprecipitation and Western blotting in vitro and in vivo. Results Among p53 mutants, p53 R213* exhibited remarkable DMARD-resistance in RAFLSs. However, AAV-induced p53 R211* overexpression ameliorated inflammatory arthritis in AIA rats without Methotrexate (MTX)-resistance, and our results discovered the immunomodulatory effect of p53 R211* via suppression of T-cell activation and T helper 17 cell (Th17) infiltration in rat joint, and finally downregulated expressions of pro-inflammatory cytokines. Total RNA sequencing analysis identified the correlation of p53 R211* with immune-related pathways. Further mechanistic studies revealed that p53 R213*/R211* instead of wild-type p53 interacted with TANK-binding kinase 1 (TBK1) and suppressed the innate immune TBK1–Interferon regulatory factor 3 (IRF3)–Stimulator of interferon genes (STING) cascade. Conclusions This study unravels the role of p53 R213* mutant in RA pathogenesis, and identifies TBK1 as a potential anti-inflammatory target.

Performance evaluation of resource-based city transformation: A case study of energy-enriched areas in Shaanxi, Gansu, and Ningxia - Qi Wen; Jie Fang; Linna Shi; Xinyan Wu; Anmeng Luo; Jinmei Ding (Journal of Geographical Sciences, 2023)

Genomic epidemiology of mcr carrying multidrug-resistant ST34 Salmonella enterica serovar Typhimurium in a one health context: The evolution of a global menace - Qixia Luo; Yuye Wu; Danni Bao; Linna Xu; Hangfei Chen; Meina Yue; Mohamed S. Draz; Yingying Kong; Zhi Ruan (Science of The Total Environment, 2023)

Combined effects of microplastics and chlortetracycline on the intestinal barrier, gut microbiota, and antibiotic resistome of Muscovy ducks (Cairina moschata) - Bing Liu; Dongyou Yu; Chaoyue Ge; Xinyu Luo; Linna Du; Xiaoping Zhang; Cai Hui (Science of The Total Environment, 2023)

Sensitivity analysis of heat transfer coefficient in primary system for LMSR core power control system based on Sobol’s method - Lehua Liang; Chuhao Li; Linna Wang; Xuejian Wang; Wenjie Zeng; Run Luo (Annals of Nuclear Energy, 2023)

cFos-ANAB: A cFos-based Web Tool for Exploring Activated Neurons and Associated Behaviors - Fan Wang; Wenjie Sun; Lei Chang; Kefang Sun; Leying Hou; Linna Qian; Chaoyin Jin; Jiandong Chen; Jiali Pu; Panmeng Ye; Shuang Qiu; Jianhong Luo; et al. (Neuroscience Bulletin, 2021)

Evaluating the suitability of TRMM satellite rainfall data for hydrological simulation using a distributed hydrological model in the Weihe River catchment in China - Haigen Zhao; Shengtian Yang; Zhiwei Wang; Xu Zhou; Ya Luo; Linna Wu (Journal of Geographical Sciences, 2015)

The effect of environmental factors on spatial variability in land use change in the high-sediment region of China’s Loess Plateau - Ya Luo; Shengtian Yang; Changsen Zhao; Xiaoyan Liu; Changming Liu; Linna Wu; Haigen Zhao; Yichi Zhang (Journal of Geographical Sciences, 2014)

Progresses on microwave remote sensing of land surface parameters - JianCheng Shi; Yang Du; JinYang Du; LingMei Jiang; LinNa Chai; KeBiao Mao; Peng Xu; WenJian Ni; Chuan Xiong; Qiang Liu; ChenZhou Liu; Peng Guo; et al. (Science China Earth Sciences, 2012)